Soldier, sailor, frogman, spy, airman, gangster, kill or die : how the allies won on D-day - Milton, Giles (Henry Hold and Company, 2018)
"Account of the first 24 hours of the D-Day invasion told by a symphony of incredible accounts of unknown and unheralded members of the Allied - and Axis - forces."--